When she rhetorically swears in Arabic: A sociolinguistic approach to women’s swearing in a university speech community - Bayoumi, Mohamed (AUC Knowledge Fountain, 2017)
Swearing, a controversial linguistic phenomenon, has recently become more of a social norm in some segments of Egyptian mass media. Much of the blame for the growth of swearing as a linguistic phenomenon, meanwhile, has been directed at mass media itself. This study investigates swearing in the speech community of female college students affiliated with the upper class in Egyptian society. The study examined the commonly-held notion that women use weaker swear words than men. Also examined were the effect of gender constellations on swear words use, and the social and linguistic functions swear words accomplish in this speech community. 154 participants responded to the study online survey and 6 of the questionnaire respondents participated in the follow-up interviews. The study, in line with Stapleton (2003), Fägersten (2012), Zawrotna (2016), and Rosenberg et al. (2017), revealed that the female speech community analyzed in this study uses swear words less frequently than males of the same speech community, yet equally offensive. Swearing takes place in both same sex and mixed gender groups. 67.2 % of participants’ swearing behavior has not been inhabited by the presence of males. While some participants in accordance with Frank and Anshen (1983) showed no change in their swearing behavior or in accordance with Jay (1986) decreased their swearing, some participants in accordance with limbrick (1991) increased their swearing in males’ presence. The study population uses swear words to express anger as well as emphasis, intimacy, humor/joy, pain, social bonding and solidarity.